2015
DOI: 10.1186/s12917-015-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as an alternative specimen for detection of Schmallenberg virus-specific antibodies in bovines

Abstract: BackgroundSchmallenberg virus (SBV), discovered in continental Europe in late 2011, causes mild clinical signs in adult ruminants, including diarrhoea and reduced milk yield. However, fetal infection can lead to severe malformation in newborn offspring. Enzyme-linked immunosorbent assays (ELISA) are commercially available for detection of SBV-specific antibodies in bovine sera and milk. Here we describe the development and evaluation of an indirect ELISA based on a yeast derived recombinant SBV nucleocapsid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this context, the IgG concentration in the oral fluid from goats is significantly lower than that in swine ( 35 ), which may explain the differences in the Se previously stated. The IgA-antibody levels in ruminants are, on the contrary, higher than in other species, which could explain the differences observed in the diagnosis when employing IgA or IgG based-ELISAs for other infections such as Schmallenberg disease ( 23 ). Moreover, recent studies support the theory that the detection of IgA in oral fluid samples appears to be more robust and stable over time in pigs ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the IgG concentration in the oral fluid from goats is significantly lower than that in swine ( 35 ), which may explain the differences in the Se previously stated. The IgA-antibody levels in ruminants are, on the contrary, higher than in other species, which could explain the differences observed in the diagnosis when employing IgA or IgG based-ELISAs for other infections such as Schmallenberg disease ( 23 ). Moreover, recent studies support the theory that the detection of IgA in oral fluid samples appears to be more robust and stable over time in pigs ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is necessary to state that, in this study, a goat model was used to evaluate the performance of the P22 ELISA when using oral fluid samples. Previous studies have shown promising results of antibody-based platforms for the diagnosis of other diseases (e.g., FMDV or SVB) when using oral fluid samples in cattle ( 22 , 23 ). The results from the present study suggest a similar or limited performance of the P22 ELISA in oral fluid samples from cattle owing to the high diagnostic pressure as a consequence of the official eradication programmes, since it is difficult to find animals in an advance stage of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 3,324,689 HIV tests conducted in the U.S. in 2011, 7% of the conventional laboratory tests (nucleic acid testing and immunoassays) and 23% of rapid antibody tests were performed on oral fluid specimens (APHL, 2013). For veterinary medicine, the detection of pathogen-specific antibodies in oral fluids has been demonstrated for rabies virus in dogs, feline immunodeficiency virus and feline leukemia virus in domestic cats, foot-and-mouth disease virus (FMDV) and Schmallenberg virus in cattle, and African swine fever virus (ASFV), FMDV, classical swine fever virus, influenza A virus (IAV), porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV), transmissible gastroenteritis virus (TGEV), porcine respiratory coronavirus (PRCV), Seneca Valley virus A (SVA), and swine vesicular disease virus in swine (Archetti et al, 1995;Lazutka et al, 2015;Prickett and Zimmerman, 2010;Rotolo et al, 2018;Senthilkumaran et al, 2017).…”
Section: Oral Fluid As a Veterinary Diagnostic Specimenmentioning
confidence: 99%